2014
DOI: 10.1001/jamaoto.2014.1705
|View full text |Cite
|
Sign up to set email alerts
|

Patients Undergoing Total Laryngectomy

Abstract: IMPORTANCE Patients undergoing total laryngectomy are at high risk for hospital readmission. Hospital readmissions are increasingly scrutinized because they are used as a metric of quality care and are subject to financial penalties. OBJECTIVE To determine the rate of, reasons for, and risk factors that predict 30-day unplanned readmission for patients undergoing total laryngectomy. DESIGN, SETTING, AND PATIENTS Retrospective cohort study at a single academic tertiary referral medical center. The study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 15 publications
4
37
1
Order By: Relevance
“…erature, most PCFs after laryngectomy usually occur within 30 days. 8,26 Because the NSQIP database is a general surgical database, it does not include procedure-specific variables for total laryngectomy; so, the variable "wound disruption" was used as a proxy for the development of a PCF. The NSQIP has 2 values for this variable: wound disruption or no complication.…”
Section: Key Pointsmentioning
confidence: 99%
“…erature, most PCFs after laryngectomy usually occur within 30 days. 8,26 Because the NSQIP database is a general surgical database, it does not include procedure-specific variables for total laryngectomy; so, the variable "wound disruption" was used as a proxy for the development of a PCF. The NSQIP has 2 values for this variable: wound disruption or no complication.…”
Section: Key Pointsmentioning
confidence: 99%
“…914 Fistula formation increases short and long term morbidity, prolongs hospitalization, and is the most common cause of wound related death in the post-surgical head and neck cancer patient. 12,1416 In response, surgeons have developed a variety of reconstructive techniques to reduce the risk of fistula, with significant institutional and surgeon variation in reconstructive patterns employed during salvage surgery. 1731…”
Section: Introductionmentioning
confidence: 99%
“…Generally, FEES has been shown to be extremely safe with all reported complications being minor and spontaneously resolved. 35 In addition, past studies indicated that the information derived from FEES facilitates the discussion between various practitioners, it does not require radiation exposure, and moreover, very severe patients can benefit from FEES. 18,20,36 These studies suggested that the FEES could be one of the most beneficial tools for accurate diagnosis of patients with dysphagia at homes or facilities.…”
Section: Discussionmentioning
confidence: 99%
“…There have been continuing discussions regarding the safety of FEES. Generally, FEES has been shown to be extremely safe with all reported complications being minor and spontaneously resolved 35 . In addition, past studies indicated that the information derived from FEES facilitates the discussion between various practitioners, it does not require radiation exposure, and moreover, very severe patients can benefit from FEES 18,20,36 .…”
Section: Discussionmentioning
confidence: 99%